Toxocara canis: migración larval y eosinofilia en el hospedador paraténico - Guardis, Mónica del Valle (2002)
The objective of this study was to analize the migratory behaviour of larvae of Toxocara canis related to eosinophilia in paratenic hosts. Mice were used as experimental models. In rodents and humans the migratory route and the pathogenesis of the parasite are similar. Balb/c mice were inoculated intragastrically with 250 (± 10) embryonated eggs. Larvae recovery: eyes and encephalon were chosen as reference organs. In the encephalon and the eye, larval recovery began in the forth and twelfth day post-inoculation respectively. The association measured by the correlation coefficient between time of observation and recovered larvae in each organ was: right eye (RE) r= 0.24; left eye (LE) r= 0.43; encephalon (E) r= 0.60. The recovery of inoculated larvae is significantly higher in the encephalon than in the eyeballs (Chi square: 185; p < 0.00001), in 80 % of mice eosinophils exceeded 6% of the formula. The correlation between eosinophilia and larval recovery in the organs observed was: 0.33 for the right eye (RE); 0.21 for the left eye (LE) and 0.44 for the encephalon; these correlation values are considered low, suggesting no association between eosinophilia and the quantity of T. canis larvae lodged in the eyes (ocular toxocarosis) or in the encephalon (cerebrospinal toxocarosis).